Midwives for Haiti. Issue 2 (March 2018) - Callister, Lynn Clark
Abstract : Our global health nursing expert, Dr. Callister, discusses an exemplary program in Haiti started by American nurse-midwives and physicians to educate birth attendants to assist women with safe care during pregnancy, birth, and postpartum.